Nitro-oleic acid inhibits vascular endothelial inflammatory responses and the endothelial-mesenchymal transition - Ambrozova, Gabriela; Fidlerova, Tana; Verescakova, Hana; Koudelka, Adolf; Rudolph, Tanja K; Woodcock, Steven R; Freeman, Bruce A; Kubala, Lukas; Pekarova, Michaela (Biochimica et biophysica acta, 2016)
BACKGROUND: Inflammatory-mediated pathological processes in the endothelium arise as a consequence of the dysregulation of vascular homeostasis. Of particular importance are mediators produced by stimulated monocytes/macrophages inducing activation of endothelial cells (ECs). This is manifested by excessive soluble pro-inflammatory mediator production and cell surface adhesion molecule expression. Nitro-fatty acids are endogenous products of metabolic and inflammatory reactions that display immuno-regulatory potential and may represent a novel therapeutic strategy to treat inflammatory diseases. The purpose of our study was to characterize the effects of nitro-oleic acid (OA-NO2) on inflammatory responses and the endothelial-mesenchymal transition (EndMT) in ECs that is a consequence of the altered healing phase of the immune response. METHODS: The effect of OA-NO2 on inflammatory responses and EndMT was determined in murine macrophages and murine and human ECs using Western blotting, ELISA, immunostaining, and functional assays. RESULTS: OA-NO2 limited the activation of macrophages and ECs by reducing pro-inflammatory cytokine production and adhesion molecule expression through its modulation of STAT, MAPK and NF-κB-regulated signaling. OA-NO2 also decreased transforming growth factor-β-stimulated EndMT and pro-fibrotic phenotype of ECs. These effects are related to the downregulation of Smad2/3. CONCLUSIONS: The study shows the pleiotropic effect of OA-NO2 on regulating EC-macrophage interactions during the immune response and suggests a role for OA-NO2 in the regulation of vascular endothelial immune and fibrotic responses arising during chronic inflammation. GENERAL SIGNIFICANCE: These findings propose the OA-NO2 may be useful as a novel therapeutic agent for treatment of cardiovascular disorders associated with dysregulation of the endothelial immune response.
Keywords: transkripční faktory STAT; Humans; Endothelial-mesenchymal transition; Endothelium, Vascular; epitelo-mezenchymální tranzice; cévní endotel; Oleic Acids; kyseliny olejové; makrofágy; Inflammation; lidé; zvířata; myši; Nitro-oleic acid; zánět; Epithelial-Mesenchymal Transition; Endothelial cells; Mice; Endothelial Cells; transformující růstový faktor beta; Smad Proteins; endoteliální buňky; MAP Kinase Signaling System; Transforming Growth Factor beta; Vascular inflammation; Nitro-fatty acids; Animals; NF-kappa B; Macrophages; proteiny Smad; MAP kinasový signální systém; STAT Transcription Factors